Between translation studies and adaptation studies: Via the case of Li Shaohong's cinematic domestication of Gabriel García Márquez's Chronicle of a Death Foretold. (1st December 2020) - Jiang, Xiaohu
This article investigates the Chinese director Li Shaohong's film Bloody Morning (1992), which was adapted from Gabriel García Márquez's novella Chronicle of a Death Foretold (1981), and the Chinese philosophical and cultural tradition that shaped this case of adaptation. By incorporating the Colombian story, Li Shaohong expressed her concern about China's backwards rural areas. Her adaptation localizes and incorporates the foreignness of the source text to meet the ideological and aesthetic horizons of expectation and the common concerns of her Chinese audience. This article argues that the director's domestication has its philosophical and cultural roots in China's history of war against foreign aggression, although the Chinese film has nothing to do with war against foreign powers.